Characterisation of Hungary's regional tourism and economic performance between 2004 and 2022 in the light of EU funding - Dr. Gyurkó, Ádám; Bujdosó, Zoltán; Rahmat, Al Fauzi; Dávid, Lóránt Dénes (Geographica Pannonica, 2024)
The objective of the study is to show the regional differences in Hungary in terms of economic determination and tourism performance. The overdominance of Budapest can be identified in most socio-economic indicators. The consequence of the capital's "hydrocephalus" is that Hungary's peripheral regions have developed serious economic challenges, and reducing regional disparities in these areas is key. From a tourism perspective in particular, the capital's hydrocephalus is also an opportunity, as the spill-over effect can increase the popularity of other destinations in the country. The Balaton and Western Transdanubia regions are the main beneficiaries of this effect. In addition to the analysis of regional disparities, the study also looks at the impact on tourism of the crisis periods caused by the 2008 global economic crisis and the pandemic that unfolded in 2020-2021, which led to a historic low in the tourism sector, notably the pandemic, by analysing longer time series data. The balance between international and domestic tourism is key to the resilience of tourism to the crisis. Multi-directional tourism can reduce exposure to external factors and contribute to the stability of the tourism industry.
Keywords: economic performance; regional differences; regional tourism performance; tourism situation assessment; tourism development